Analysis of Language Variety in The Indonesian Islamic Student Movement PMII Commisariat Hasyim Asy'ari - Nasarudin, M; Udjang Pairin M.Basir (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Language style is also able to enable a person to relate what he is thinking to the person he is speaking to, and can even influence the thoughts and feelings of the person he is speaking to. As is the case in the Indonesian Islamic student movement which has many different language styles. The language used during formal, informal and non-formal activities has differences or variations, especially when compared with students who are not members of the Indonesian Islamic Student Movement, for example the language "Greetings of Movement" in this diction is a greeting to a meeting between fellow members.